(untitled) (Scientific journal of the Fergana State University, 2024)
The article focuses on the gradual improvement of the image of the pomegranate in Uzbek poetry based on traditionalism. In the introduction, the importance of the problem is discussed. In the analysis of literature, the opinions of scientists about tradition and innovation were analyzed, and essential scientific-theoretical views were recognized as a methodological basis. In the discussion part, the artistic-aesthetic function of the image of the pomegranate in the folk creativity is analyzed on the example of proverbs and folk songs, furthermore, its traditionality in written literature is reviewed in the poems of Alisher Navoi, Uvaisiy, Abdulla Oripov, Shavkat Rahmon. At the end of the article, the conclusions which are based on result of the research are clearly and succinctly expressed. References are listed in 13 titles.